Antiques ravin' - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2019)
After being elected county sheriff, Vivian Borne deputizes her reluctant daughter to help solve a series of murders centered around the town's Edgar Allan Poe festival.